Performance improvement through scalable design of mutli-link 2-DOF automated pedestrian crowd control barriers - Shorrab., Shady S.; Shafie, Amir Akramin; Alang Rashid, Nahrul Khair (Asian Research Publishing Network, 2016)
This paper describes the performance improvement through scalable design of a two degree of freedom (DOF) automated pedestrian crowd control barrier based on a closed-loop feedback control system. Since most of the barriers existing amd used is immobile, static and not adaptable to changing crowd condition. In the proposed experiment, a scalable design of an adaptive system that can assume strictly the role of the security man by sensing the crowd and move away to provide a safe area between crowd people and events area without collision. Kinematic and dynamic analysis to build the system is proposed, while planning trajectory is provided by suggesting some cases to control a specific current crowd situation using Computed Torque Controller (CTC), which identifies the difference between the input desired trajectory with the newly collected data of the equation of motion and dynamic equation analysis of the actual system to achieve a good and accuracy results by reducing the error and minimize the disturbances. Simulation studies for a straightforward range of motion exercise were carried out, and experimental validation for the automated barrier with two DOF is performed to move the system forward and backward and avoid any obstacle on its path. The results obtained shows that the controller can track the desired position and trajectories for the barriers system motion, and adequately adapt the control parameters to the crowd conditions and the sensor and motor control performance.